Geoestatística aplicada ao monitoramento de águas subterrâneas no município de Itacoatiara/AM - Mitouso, Daiana Thalisy da Silva (Brasil, 2023)
The lack of basic sanitation generates in the great aquatic matrices of the Amazon. The municipality of Itacoatiara is a reflection of this situation, realizing inefficiency in its aspects of sanitation. The catchment of supply, of water supply is mainly the simplest and smallest supply system, it is used in many cities of Itacoatiara that is not used for the supply of supply. The Autonomous Water and Escheto System - SAAE performs monitoring and analysis of the parameters of turbidity, chlorine, heterotrophic bacteria, total coliforms and Escherichia Coli, pH, in the monitoring wells and water. Comparing with Ordinance GM/MS No. 888/2021 responsible agency SAAE presents some flaws in the management of groundwater for supply. In order to improve the monitoring of sampling points and create an information base, interpolation was performed using the Inverse Weighted Distance - IDP, for the turbidity and pH parameters at powers 2 and 3, followed by the verification of accuracy. These processes were carried out in the RStudio software, which indicated the power 3 as the one that best fits the IDP model. Subsequently, thematic maps of the parameters analyzed were made using the Qgis software. The results indicated that Araújo Costa, Novo Horizonte, Jardim Florestal and Mamoud Amed have turbidity levels higher than those allowed by legislation. Likewise, it was identified that the Novo Horizonte, Mamoud Amed and Da Paz neighborhoods have more acidic waters, in a pH range of 4.4 to 6.0.